Cross-Country Analysis of the Impact of Corruption and Other Factors on Youth Presence in Parliament - Assel Bekenova (Journal of Contemporary Governance and Public Policy, 2022)
The purpose of research is to study the influence of corruption and other factors on the presence of young people in formal politics. The motivation for the study of this issue was the decrease in the representation of youth in the traditional district and republican parliaments due to the existence of different determinants. Such a decrease, as a rule, affects the socio-economic indicators of most countries, since it is the youth who are the socially active, able-bodied segment of the population, whose support young people must find from the youth parliament representing their interests and needs. Corruption is considered to be the main reason for this decline. To prevent this, asian states such as Singapore, Hong Kong, Thailand and South Korea introduced institutional measures in the form of establishing an anti-corruption agency or other developed and developing countries carried out legislative anti-corruption reforms, which, on the contrary, led to counter productiveness due to excessive regulation. Thus, we will check whether the factor of corruption is indeed a significant variable influencing the presence of young people in parliament or whether the existence of other factors is more important. To test the main hypothesis, namely the negative relationship between the factor of corruption and the share of youth in parliament, we have analysed data from 90 countries based on the regression analysis method. The results showed that corruption is not a statistically significant variable, i.e., it does not have a significant impact on the political presence of young people in politics. The education factor showed a statistically significant result, which is logical since politically educated young people are most often active in politics, as a rule they become potential candidates for deputies either through youth wings or through non-state youth associations. Therefore, it seems important in public policy to increase political competitiveness to develop the potential of education.